The Berenstain Bears and the galloping ghost - Berenstain, Stan, 1923-; Berenstain, Jan, 1923- (New York : Random House, 1994)
Brother Bear learns about fear and getting back in the saddle when a ghost haunts the riding academy.
660
660
Accelerated Reader AR
Keywords: Bears -- Fiction; Fear -- Fiction; Horsemanship -- Fiction; Ghosts -- Fiction